A Rapid HPLC-UV Protocol Coupled to Chemometric Analysis for the Determination of the Major Phenolic Constituents and Tocopherol Content in Almonds and the Discrimination of the Geographical Origin - Natasa P. Kalogiouri; Petros D. Mitsikaris; Dimitris Klaoudatos; Athanasios N. Papadopoulos; Victoria F. Samanidou (Molecules, 2021)
Reversed phase-high-pressure liquid chromatographic methodologies equipped with UV detector (RP-HPLC-UV) were developed for the determination of phenolic compounds and tocopherols in almonds. Nineteen samples of Texas almonds originating from USA and Greece were analyzed and 7 phenolic acids, 7 flavonoids, and tocopherols (−α, −β + γ) were determined. The analytical methodologies were validated and presented excellent linearity (r2 > 0.99), high recoveries over the range between 83.1 (syringic acid) to 95.5% (ferulic acid) for within-day assay (n = 6), and between 90.2 (diosmin) to 103.4% (rosmarinic acid) for between-day assay (n = 3 × 3), for phenolic compounds, and between 95.1 and 100.4% for within-day assay (n = 6), and between 93.2–96.2% for between-day assay (n = 3 × 3) for tocopherols. The analytes were further quantified, and the results were analyzed by principal component analysis (PCA), and agglomerative hierarchical clustering (AHC) to investigate potential differences between the bioactive content of almonds and the geographical origin. A decision tree (DT) was developed for the prediction of the geographical origin of almonds proposing a characteristic marker with a concentration threshold, proving to be a promising and reliable tool for the guarantee of the authenticity of the almonds.